Pengaruh Kompetensi Akuntansi, Pemahaman Standar Audit, dan Independensi Auditor terhadap Penggunaan Aplikasi Audit (ATLAS) - Syalia Masarrah; Sjarief Hidajat (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
Technology is growing rapidly and followed by economic growth. Auditors are required to upgrade themselves to keep up with the developments of the times. The Financial Profession Building Centre (PPPK) and the Ministry of Finance have launched an audit software called ATLAS (Audit Tool and Linked Archive System) which can be an audit assistant tool for carrying out the entire audit process. Based on Davis's theory of the Technological Acceptance Model (TAM), which states that external factors, usability perception and ease of use, attitudes and initial purpose of use influence the acceptance of technology. This is what makes researchers choose accounting competence factors, an understanding of audit standards, and whether auditor independence influences when using the ATLAS application. Quantitative method with statistical research with data collection techniques using questionnaires. The results of this study showed that the three factors had a significant influence on the use of ATLAS applications obtained from 29 respondents sampled.